Comparison on self - and superior ratings of job performance of nurses: a Malaysian study - Ali, Hassan; Othman, Noraini (International Academy of Business and Economics, 2008)
This study is undettaken to compare self-and superior ratings of job performance among hospital nurses in Malaysia. The study comprised 580 nurses and 70 sisters. A total of 580 matched pairs of superior and subordinate evaluations job performance were obtained in the study. Job performance was measured using three dimensions; job outcome, skill and knowledge, and personal quality. The nurses included in the study provided self- ratings for job performance. The sisters who supervise these nurses provided ratings on job performance of the nurses. The results indicate that there were significant differences in the mean ratings between superior and subordinates for all dimensions of job performance.Superior ratings for all dimensions of job performance were significantly higher than self-ratings.